An Ecocritical Study of Mary Oliver's Poetry - Asst.Prof. Shireen Shihab Hamad [Ph.D]; Tabarak Sadiq Ali (Journal of College of Education, 2023)
The loss of interconnectedness, unity, and harmony between nature and man has been one of the most significant consequences of the industrial revolution and technological advancement in modern times. Due to this degradation of nature, human health suffers as a result. In this context, finding an effective method to re-establish the connection between the ecosystem and humans is critical. Ecocriticism is achieving this purpose efficiently because it involves exploring the relationship between literature and the natural world. Based on the fact that poetry is an effective tool for spreading environmental awareness among people. The application of this theory will be within the framework of American poetry represented by Mary Oliver(1935-2019), using eco critical perspective, through the examination and analysis of her poetry by explaining how she finds a way in reuniting with nature.
Keywords: Ecocriticism, Nature, the Self, Mary Oliver.